Does energy-consuming right trading policy achieve a low-carbon transition of the energy structure? A quasi-natural experiment from China - Ye Chen; Bin Zhong; Bingnan Guo (Frontiers in Environmental Science)
IntroductionThe implementation of energy-consuming right trading (ECRT) policy in 2017 is a major measure to promote the construction of ecological civilization and green development, which also aligns with the global trend towards sustainable energy management and carbon emission reduction.MethodsBased on energy consumption data in China from 2010 to 2021, this paper utilizes the Difference-in-Differences (DID) method to assess the extent and process of the impact of energy consuming right trading policy on the low-carbon transition of the energy structure. The transmission mechanism of industrial structure upgrading and the new-quality productive forces in the impact process was discussed, and the regulatory role of environmental regulations was tested.ResultsThe findings indicate: 1) ECRT has a strong driving effect on the low-carbon transition of the energy structure. 2) ECRT can promote low-carbon transition of the energy structure through the dual channel of promoting industrial structure upgrading and new quality productive forces. 3) The influence of ECRT on the low-carbon transition of the energy structure is different in different regions, and the higher degree of industrial agglomeration and renewable energy-rich regions are more significantly promoted by new quality productivity. 4) Environmental regulation has a significant positive moderating effect on the relationship between ECRT and low-carbon transition of the energy structure. 5) Furthermore, the exploratory analysis reveals that the positive impacts of ECRT policies on the low-carbon Transition of the energy structure translates into higher green total factor productivity and lower environmental pollution, which promotes the sustainable development of the low-carbon Transition of the energy structure.DiscussionThis paper responds to the basic question of whether energy use rights policies can promote the low-carbon Transition of the energy structure, and provides empirical evidence and policy reference not only for the development of China’s environmental policy and the direction of energy consumption but also for the international community’s efforts in sustainable energy and environmental governance.